Leveraging Value of Disparate Information Assets XML to the rescue. - Huck, Kevin
Businesses today are trying to cope with an overabundance of electronic information. Beyond the silos of structured data that have been managed with traditional database technologies is a need to manage the ever-increasing deluge of unstructured data types and sources. E-mails, spreadsheets, office documents, HTML files and so on, contain a wealth of information, but are not easily accessible across the organization.